Pullulan hydrogels as drug release platforms in biomedicine - Teixeira, Marta Sofia Aguiar Carvalho Oliveira (2023)
It is increasingly urgent to develop new therapeutic systems to combat the spreading and evolution of various pathologies globally. Nonspecific therapies and/or insufficient medication biodistribution might hinder the patient's recovery. In this sense, a targeted and controlled delivery of various biomolecules allows overcoming the limitations of conventional delivery systems, taking the user one step closer to the successful treatment of a disease. Hydrogels have been highlighted for their drug delivery abilities, particularly for their tunable properties, like hydration capacity, biodegradability, release kinetics, etc., that can be adjusted to the desired needs. Additionally, they can be produced from either natural and/or synthetic polymers, with natural-origin sources providing exceptional features like biodegradation and acceptable integration in biological systems. One of those polymers is pullulan, a biodegradable, biocompatible and hemocompatible material, with multiple uses in biomedicine. Investigations into pullulan-based hydrogels have progressively increased over the last few decades. This review addresses the uses of pullulan in biomedical engineering, emphasizing its exceptional properties for drug delivery and its processing into hydrogel systems, either in its original or derivative forms.